Cortisol and pregnenolone as diagnostic criteria for evaluating the duration of dying of a person at the early stages of antemortem period. - Bilyakov, A. M. (Морфологія / Morphologia / Morfologìâ, 2012)
The content of cortisol and its precoursor pregnenolone in adrenal tissue was evaluated with the purpose of determining the duration of dying of a human being influenced by a lethal traumatic factor. It is shown that pregnenolone as an intermediate component of steroidogenesis is not identified in adrenal tissue of the persons who died as a result of a traumatic factor influence. The amount of cortisol in adrenal tissue differs depending on the duration of dying of a person and can be used as a diagnostic criterion for evaluating the duration of dying of the person at an early stage of antemortem period.